2005
DOI: 10.1128/mcb.25.19.8748-8754.2005
|View full text |Cite
|
Sign up to set email alerts
|

Human DNA Polymerase ι Promotes Replication through a Ring-Closed Minor-Groove Adduct That Adopts a syn Conformation in DNA

Abstract: Acrolein, an ␣,␤-unsaturated aldehyde, is generated in vivo as the end product of lipid peroxidation and from oxidation of polyamines. The reaction of acrolein with the N 2 group of guanine in DNA leads to the formation of a cyclic adduct, ␥-hydroxy-1,N 2 -propano-2-deoxyguanosine (␥-HOPdG). Previously, we have shown that proficient replication through the ␥-HOPdG adduct can be mediated by the sequential action of human DNA polymerases (Pols) and , in which Pol incorporates either pyrimidine opposite ␥-HOPdG, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
59
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(68 citation statements)
references
References 29 publications
9
59
0
Order By: Relevance
“…It relies on Hoogsteen base pairing as opposed to typical WatsonCrick base pairing and thus operates with very low fidelity [107]. This mechanism may facilitate read-through of replication-blocking minor groove purine adducts [108]. In vivo, uracil derived from cytosine deamination may be the desired target of Polι as it inserts a G opposite a template U [109].…”
Section: Y Family Dna Polymerasesmentioning
confidence: 99%
“…It relies on Hoogsteen base pairing as opposed to typical WatsonCrick base pairing and thus operates with very low fidelity [107]. This mechanism may facilitate read-through of replication-blocking minor groove purine adducts [108]. In vivo, uracil derived from cytosine deamination may be the desired target of Polι as it inserts a G opposite a template U [109].…”
Section: Y Family Dna Polymerasesmentioning
confidence: 99%
“…In contrast to the inhibitory effects of the ring-closed analog of ␥-HOPdG on DNA synthesis by the various TLS Pols, the permanently ring-opened form of ␥-HOPdG does not present a significant block to synthesis by Pols , , or , as they can each carry out both nucleotide incorporation and the extension reactions opposite from it (33,54). Thus, we assume that an N 2 -dG minor-groove adduct, such as the ring-open form of ␥-HOPdG, can be accommodated in the active site of these Pols at both the nucleotide insertion and subsequent extension steps.…”
mentioning
confidence: 99%
“…Studies with the permanently ring-opened or ring-closed structural analogs of ␥-HOPdG have yielded useful information about the relative abilities of Pols , , and to replicate through such N 2 -dG adducts, and the combined results of these and other studies have indicated that these Pols vary in their response to different N 2 -dG adducts. For example, the ring-closed form of ␥-HOPdG is a strong block for nucleotide incorporation by Pols and , with only Pol being capable of inserting a C opposite from it (33,54). And, even though Pol can extend from a C opposite ␥-HOPdG, which can adopt both the ring-opened and ring-closed forms (51), it is unable to extend from the permanently ring-closed analog of ␥-HOPdG (54), suggesting that Pol can extend only if ␥-HOPdG is in the ring-opened conformation.…”
mentioning
confidence: 99%
“…1), have yielded the following observations and conclusions (28,30). (i) The ring-open form of ␥-HOPdG is not a block to synthesis by human Pol, Pol, or Pol at either the nucleotide incorporation step or the extension step.…”
mentioning
confidence: 99%
“…Since ␥-HOPdG can adopt a ring-closed cyclic form or a ring-open form in DNA, we also examined the ability of human Y family Pol (17) and Pol and Pol (30) to replicate through the structural analogs of ␥-HOPdG which permanently stay in the ring-closed or the ring-open form (Fig. 1).…”
mentioning
confidence: 99%